Makna Simbolik Tradisi Sedekah Bumi Kramat di Desa Jayabakti Kecamatan Cabangbungin Bekasi - Karimah, Iin Inayatul; Sari, Trie Yunita (Inklusiva: Jurnal Studi Agama-Agama, 2024)
This research examines the meaning of symbols that emerge from the Earth Kramat Batok Charity Tradition. This research is motivated by the author's interest in the earth alms tradition, which is a form of traditional ritual for the people on the island of Java that has been passed down from generation to generation from the ancestors of the ancient Javanese. Interestingly, the Earth Almsgiving tradition is also carried out in the Bekasi area, which is located in Jayabakti Village, Branchbungin District, Bekasi. Bekasi is a city known as an industrial city the conclusion of this research is knowing how the earth almsgiving tradition procession is carried out and knowing what meanings are contained in this tradition.